Association between Prior Chlamydia trachomatis Infection and Ectopic Pregnancy at a Tertiary Care Hospital in South Western Uganda - Derrick Paul Mpiima; George Wasswa Salongo; Henry Lugobe; Augustine Ssemujju; Olivier Mumbere Mulisya; Abraham Masinda; Hillary Twizerimana; Joseph Ngonzi (Hindawi Limited, 2018)
Background. Increase in the number of ectopic pregnancy is attributed to increase in the incidence of pelvic infections. Chlamydia trachomatis is responsible for most of the sexually transmitted bacterial infections. If undetected and untreated, the infection can ascend to the upper genital tract and cause pelvic inflammatory disease (PID) and related sequelae (ectopic pregnancy and tubal factor infertility). Objective. To determine the association between prior Chlamydia trachomatis infection and ectopic pregnancy at Mbarara Regional Referral Hospital (MRRH). Methods. This was an unmatched case-control study carried out at MRRH involving 25 cases and 76 controls. Serological evidence of prior chlamydial infection was determined by testing for the presence of Chlamydia immunoglobulin G antibodies in their blood. Logistic regression was used to determine the association between prior Chlamydia trachomatis infection and also the factors associated with ectopic pregnancy. The significant level of <0.05 was used. Results. Chlamydia antibodies were found in 60% of patients with ectopic pregnancy and 26.3% of the controls (p=0.002). The presence of Chlamydia antibodies was associated with a fourfold risk of ectopic pregnancy. Conclusion. There was a strong association between prior Chlamydia trachomatis infection and ectopic pregnancy.